Inhalation health risk assessment of ambient PM2.5 and associated trace elements in Cape Town, South Africa. Issue 8 (14th September 2022) - Alfeus, Anna; Molnar, Peter; Boman, Johan; Shirinde, Joyce; Wichmann, Janine
Abstract: Few human health risk assessment studies of air pollution exist in Africa. This study used the US EPA health risk framework to investigate the human health risks due to inhalation exposure to ambient PM2.5 and some of its trace element composition (Cl, Si, and Ti) in Cape Town, South Africa, for 12 months (April 2017 to April 2018). The safe average daily dose was determined using the yearly WHO guideline and South African ambient air quality standard for PM2.5 and the US EPA regional screening levels for trace elements. The average yearly PM2.5 concentration (13 µg/m 3 ) was above the yearly WHO guideline (5 µg/m 3 ), but below the yearly South African standard (20 µg/m 3 ). The average yearly PM2.5 concentration posed a low risk to adults (Hazard Quotient = 0.66) compared to infants (HQ = 2.13) and children (HQ =1.96). Cl posed health risks to all age groups (HQ > 1). The study concludes that PM2.5 and its trace element components pose adverse health effects to all population age groups. The toxicity of PM2.5 depends on its composition; hence this study recommends a source apportionment study to quantify the source contributions and inform the right abatement strategies.